ANALYSIS OF ENERGY DEMAND IN INDONESIA - Pinasti Nur Islami; Jariah Abubakar (RADJA PUBLIKA, 2025)
The purpose of this study is to determine the Influence of Energy Supply, Energy Needs and Final Energy on Energy Demand in Indonesia. The study uses Time Series data from 1985-2023. The study uses the Autoregressive Distributed Lag (ARDL) method. The results of the short-term study show that the Energy Supply variable has a negative and insignificant effect on Energy Demand in Indonesia, Energy Needs has a negative and significant effect on energy demand in Indonesia, and the final energy variable has a positive and insignificant effect on Energy Demand in Indonesia. In the long term, the energy supply and energy needs variables have a negative and significant effect on energy demand in Indonesia. The final energy variable has a positive and significant effect on energy demand in Indonesia.